Comparative effectiveness of gemcitabine plus cisplatin versus methotrexate, vinblastine, doxorubicin, plus cisplatin as neoadjuvant therapy for muscle‐invasive bladder cancer. Issue 15 (14th April 2015) - Galsky, Matthew D.; Pal, Sumanta K.; Chowdhury, Simon; Harshman, Lauren C.; Crabb, Simon J.; Wong, Yu‐Ning; Yu, Evan Y.; Powles, Thomas; Moshier, Erin L.; Ladoire, Sylvain; Hussain, Syed A.; Agarwal, Neeraj; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Gemcitabine plus cisplatin (GC) has been adopted as a neoadjuvant regimen for muscle‐invasive bladder cancer despite the lack of Level I evidence in this setting. METHODS Data were collected using an electronic data‐capture platform from 28 international centers. Eligible patients had clinical T‐classification 2 (cT2) through cT4aN0M0 urothelial cancer of the bladder and received neoadjuvant GC or methotrexate, vinblastine, doxorubicin, plus cisplatin (MVAC) before undergoing cystectomy. Logistic regression was used to compute propensity scores as the predicted probabilities of patients being assigned to MVAC versus GC given their baseline characteristics. These propensity scores were then included in a new logistic regression model to estimate an adjusted odds ratio comparing the odds of attaining a pathologic complete response (pCR) between patients who received MVAC and those who received GC. RESULTS In total, 212 patients (146 patients in the GC cohort and 66 patients in the MVAC cohort) met criteria for inclusion in the analysis. The majority of patients in the MVAC cohort (77%) received dose‐dense MVAC. The median age of patients was 63 years, they were predominantly men (74%), and they received a median of 3 cycles of neoadjuvant chemotherapy. The pCR rate was 29% in the MVAC cohort and 31% in the GC cohort. There was no significant difference in the pCR rate when adjusted for propensity scores between the 2 regimens (odds ratio, 0.91; 95% confidence interval, 0.48‐1.72; P = .77). In an exploratory analysis evaluating survival, the hazard ratio comparing hazard rates for MVAC versus GC adjusted for propensity scores was not statistically significant (hazard ratio, 0.78; 95% confidence interval, 0.40‐1.54; P = .48). CONCLUSIONS Patients who received neoadjuvant GC and MVAC achieved comparable pCR rates in the current analysis, providing evidence to support what has become routine practice. Cancer 2015;121:2586–2593. © 2015 American Cancer Society.